The Teacher Strategies in Addressing Reading Difficulties in Second-Grade Elementary School Students - Hasanah, Ghoniatul Ilmi; Dafit, Febrina (The Future of Education Journal, 2025)
The second-grade teacher has implemented various guided reading strategies; however, these efforts have not been optimal. Students who face reading difficulties are still unable to understand simple words and sentences, thus basic reading skills remain a barrier. This study aims to describe the teacher's strategies in overcoming reading difficulties among second-grade students at SDN 01 Muara Kelantan, Siak Regency. This research is qualitative in nature with a case study approach. The data sources in this study include both primary and secondary data. Primary data involves the second-grade teacher and students, while secondary data includes test scores, photos, video recordings of observations, and teaching modules. The data collection techniques and instruments used in this study are interview guides, observation guides, and documentation review sheets. Data analysis in this study follows the Miles and Huberman model through three stages: data reduction, data presentation, and drawing conclusions. Based on the research results, it can be concluded that the teacher's strategies in overcoming reading difficulties for second-grade students at SDN 01 Muara Kelantan are carried out systematically and responsively to the students' needs. Some of the strategies employed by the teacher include using engaging and effective learning media, applying reading methods, boosting students' confidence and motivation, refraining from blaming students for their difficulties, and implementing a special remedial program.